2017
DOI: 10.22159/ajpcr.2017.v10i3.15925
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of Grinding and Slurry Method on Physicochemical Characteristic of Acyclovir – Succinic Acid Cocrystal

Abstract: Objective: This study aimed to compare the characteristics of acyclovir (ACV)-succinic acid (SA) cocrystal with grinding and slurry method.Methods: Cocrystals were prepared using grinding and slurry methods. Physicochemical characterizations were performed using powder X-raydiffraction (PXRD), differential scanning calorimetry, Fourier transform infrared (IR) spectroscopy, scanning electron microscope (SEM), anddissolution test.Results: The study revealed that cocrystal of ACV-SA showed a decrease in the melti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This study herein does not address other factors that are relevant from a practical utility perspective, including crystallinity, particle size, and bulk purity, each of which can impact dissolution rate and tabletability. 72 For example, Rahman and co-workers 73 compared the dissolution rate of an acyclovir-succinic acid cocrystal made via either slurrying or grinding. They reported that the cocrystal formed by slurrying exhibited a faster dissolution rate compared to the poorly crystalline product afforded by grinding.…”
Section: Resultsmentioning
confidence: 99%
“…This study herein does not address other factors that are relevant from a practical utility perspective, including crystallinity, particle size, and bulk purity, each of which can impact dissolution rate and tabletability. 72 For example, Rahman and co-workers 73 compared the dissolution rate of an acyclovir-succinic acid cocrystal made via either slurrying or grinding. They reported that the cocrystal formed by slurrying exhibited a faster dissolution rate compared to the poorly crystalline product afforded by grinding.…”
Section: Resultsmentioning
confidence: 99%
“…It is known to be ecofriendly method for industrial-level production due to less amount of solvent used. The process does not also depend on the temperature, and more importantly, it diminishes the chances of unwanted solvate formation, adefovir dipivoxil-glutaric acid cocrystal [27] and quercetinsuccinic acid cocrystal improves solubility and dissolution rate by 1.62 and 1.25, respectively.…”
Section: Liquid-assisted Grinding Methodsmentioning
confidence: 99%
“…fig. 4 (B)-(D) From XRD spectra it was observed and concluded that, the intensity and number of peaks were reduced in the XRD spectra of Carvedilol co-crystals compare to pure Carvedilol indicate that the reduction in crystallinity and formation of new bonding in the co-crystals This variation in the XRD pattern of pure Carvedilol and its Co-crystals due to changes in the crystal lattice structure of drug and conformer [19].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%